Streptomyces antarcticus sp. nov., isolated from Horseshoe Island, Antarctica - Sahin, Sibel Melisa; Saticioglu, Izzet Burcin; Duman, Muhammed; Ay, Hilal (MICROBIOLOGY SOC, 2025)
Three novel actinobacterial strains, H27-S2T, H34-AA3 and H34-S5, were isolated from soil samples collected on Horseshoe Island, Antarctica, as part of an effort to discover new Streptomyces species with industrial and pharmaceutical relevance. A genome-based comparative analysis was conducted to characterize the strains. The pairwise comparisons of the 16S rRNA gene sequences confirmed their affiliation with the genus Streptomyces, with the highest sequence identity values of 99.7-99.8% with Streptomyces avidinii NBRC 13429T. However, genome-based taxonomic analyses, including digital DNA-DNA hybridization and average nucleotide identity analyses, confirmed that these strains represent a novel species within the genus Streptomyces. A comprehensive genome annotation revealed that the strains possess extensive biosynthetic capabilities, particularly for secondary metabolites, antimicrobial resistance mechanisms, heavy metal resistance genes and stress adaptation systems for survival in cold environments. Their metabolic potential includes aromatic compound degradation, indicating a promising role in bioremediation, while their secondary metabolite gene clusters suggest potential applications in pharmaceutical and clinical research. Given their ability to thrive in extreme Antarctic conditions, these strains may contribute to advancements in cryotechnology and enzyme production for industrial applications. Based on phylogenomic analyses, these strains represent a novel Streptomyces species, for which the name Streptomyces antarcticus sp. nov. is proposed. The type strain is H27-S2T (=DSM 114983T=CGMCC 4.7867T).
Keywords: Actinomycetota; Antarctica; biosynthetic gene clusters; genomics; polyphasic taxonomy; GENE SEQUENCE SIMILARITY; DNA-DNA HYBRIDIZATION; MECHANISM; IDENTIFICATION; DISCOVERY; PROTEASE; BIOLOGY; CLUSTER; VALUES; Microbiology